How to encourage lecturer performance in research through servant leadership, organizational commitment, and tacit knowledge sharing - Alex Winarno; Deni Hermana (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
The purpose of the present study was to analyze the role of servant leadership, organizational commitment, and tacit knowledge sharing in enhancing research performance. To this end, a survey of 400 randomly recruiting private university lecturers was conducted. The data were analyzed by using SEM covariant. The analysis result showed that leadership that tends to exhibit service and sacrifice towards its subordinate improved organizational commitment, particularly in the continuance and normative dimensions. Tacit knowledge sharing was found to promote the affective dimension of lecturers' corporate responsibility to research performance. Tacit knowledge sharing plays a mediating role between servant leadership and commitment organization and research performance. It was found to determine the research performance. The present study calls for knowledge management for tacit knowledge sharing to improve performance from a theoretical perspective. This can be done by focusing on tacit knowledge sharing about research, especially concerning research methodology and practical method development. From a practical standpoint, the study calls for extending and developing a structured tacit knowledge sharing supported by sharing culture among the lecturers.